A spatial agent-based simulation model for malaria epidemiology : design, implementation, and applications for malaria epidemiology /: design, implementation, and applications for malaria epidemiology. (2015) - Arifin, S.M. Niaz; Madey, Gregory R; Collins, Frank H
No abstract available